Strategi Guru Dalam Pembelajaran Al-Qur’an Melalui Metode At-Tartil - Ziadatun Nafisah (Impressive: Journal of Education, 2024)
As a Muslim we have a guide in life, namely the holy book of the Qur'an, so this is an obligation for every Muslim to study the Qur'an and practice it in everyday life. Learning the Qur'an is a process that produces changes and the ability to pronounce words, or the letters of the Qur'an starting with the letter "alif" to the letter "yes" which he sees by exerting several actions. In learning the Qur'an there are several ways or steps that are arranged in a planned and systematic manner, with the use of techniques or methods in the Qur'an learning process to be able to achieve the desired goals in the Qur'an learning process. The Tartil method is a method of learning the Koran, by reading the Koran slowly and slowly and pronouncing the letters of the Makhraj correctly. The objectives of this study are 1. To describe the teacher's strategy in learning the Qur'an at TPQ Al-Ikhas in Baujeng Village, Beji District, Pasuruan Regency. 2. To determine the reading ability of students at TPQ al-ikhlas, Baujeng village, Beji sub-district in learning the Qur'an using the at-tartil method. 3. To find out the implementation of the tartil method in learning the Qur'an at TPQ Al-ikhlas in Baujeng Village, Beji District, Pasuruan Regency. The research method used is a qualitative research method with data collection techniques that use the method of observation, interviews and documentation. The interview technique consists of several informants. Based on the results of the study, it can be concluded that the TPQ al-ikhlas institution uses several strategies in the implementation of al-Qur'an learning, one of which is the at-tartil method. In the process of its application, it can be seen that the students have been able to practice how to read the Qur'an well, and in reading it is fluent and correct in accordance with the science of recitation. The Makhorijul letters are correct, but there are some students who cannot correctly pronounce the letters.